2014
DOI: 10.1007/s00424-014-1464-8
|View full text |Cite|
|
Sign up to set email alerts
|

Exercise training in adverse cardiac remodeling

Abstract: Cardiac remodeling in response to a myocardial infarction or chronic pressure-overload is an independent risk factor for the development of heart failure. In contrast, cardiac remodeling produced by regular physical exercise is associated with a decreased risk for heart failure. There is evidence that exercise training has a beneficial effect on disease progression and survival in patients with cardiac remodeling and dysfunction, but concern has also been expressed that exercise training may aggravate patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 114 publications
1
11
0
Order By: Relevance
“…It is now clear that exercise exerts a number of beneficial effects in CHF, including an improvement of skeletal muscle perfusion, and metabolism, breathing efficiency, and neurohumoral activation [ 1 ]. More recent evidence indicates that exercise training in patients with CHF also improves cardiac function [ 2 ], which is in agreement with observations in animal models of CHF and appears mediated by exercise-induced amelioration of CHF-associated interstitial fibrosis and cardiomyocyte dysfunction and apoptosis [ 3 ]. These beneficial effects of exercise are the consequence of the activation of different molecular signalling pathways that drive the transcriptional control of cardiac remodelling in exercise training versus CHF [ 1 , 3 , 4 ].…”
supporting
confidence: 83%
“…It is now clear that exercise exerts a number of beneficial effects in CHF, including an improvement of skeletal muscle perfusion, and metabolism, breathing efficiency, and neurohumoral activation [ 1 ]. More recent evidence indicates that exercise training in patients with CHF also improves cardiac function [ 2 ], which is in agreement with observations in animal models of CHF and appears mediated by exercise-induced amelioration of CHF-associated interstitial fibrosis and cardiomyocyte dysfunction and apoptosis [ 3 ]. These beneficial effects of exercise are the consequence of the activation of different molecular signalling pathways that drive the transcriptional control of cardiac remodelling in exercise training versus CHF [ 1 , 3 , 4 ].…”
supporting
confidence: 83%
“…In addition to the stimulation of eNOS, EX beneficially influences the cardiac nitroso–redox balance by activating reactive oxygen species (ROS) scavenger enzymes such as superoxide dismutases (SODs) [ 14 , 15 ]. Accordingly, we and others have demonstrated that EX improves survival and attenuates LV dysfunction, oxidative stress, and fibrosis in a mouse model of myocardial infarction (MI) [ 16 , 17 , 18 , 19 ], and have additionally demonstrated that full eNOS expression is required for these beneficial EX effects after MI [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of exercise during conditions characterized by persistent left ventricular pressure-overload such as aortic stenosis remains unsettled. As life expectancy is increasing and aortic stenosis prevalence augments with age, the number of patients with pressure-overload-induced heart failure will grow [ 17 ]. Experimental studies on the effects of exercise on cardiac and skeletal muscle during aortic stenosis have shown controversial results.…”
Section: Introductionmentioning
confidence: 99%